2012
DOI: 10.1007/s13197-012-0781-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of added herb extracts on oxidative stability of ghee (butter oil) during accelerated oxidation condition

Abstract: The antioxidant activities of vidarikand (Pueraria tuberosa), shatavari (Asparagus racemosus) and ashwagandha (Withania somnifera) extracts (aqueous and ethanolic) were evaluated and compared with BHA using β-carotene bleaching assay, DPPH assay and Rancimat method. Phenolic contents of ethanolic extracts of herbs were high compared to their aqueous extracts. The ethanolic extracts showed more antioxidant activity (β-carotene-linoleic acid model system) than their aqueous counterparts. In DPPH system also, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…Karaaslan et al (2011) also found higher antioxidant power in grape extract fortified yogurt with higher anthocyanin content than control yogurt. Pawar et al (2012) incorporated different herbs into ghee and they found that antioxidative activity of the herbs decreased in the order-vidarikand (Pueraia tuberosa)>ashwagandha>-shatavari. Modi (2009) reported that the incorporation of mango pulp enhanced the antioxidant activity of sweetened mango dahi by1.64 fold as compared to control sweetened dahi.…”
Section: Total Antioxidant Capacity (Tac) By Abts Methodsmentioning
confidence: 99%
“…Karaaslan et al (2011) also found higher antioxidant power in grape extract fortified yogurt with higher anthocyanin content than control yogurt. Pawar et al (2012) incorporated different herbs into ghee and they found that antioxidative activity of the herbs decreased in the order-vidarikand (Pueraia tuberosa)>ashwagandha>-shatavari. Modi (2009) reported that the incorporation of mango pulp enhanced the antioxidant activity of sweetened mango dahi by1.64 fold as compared to control sweetened dahi.…”
Section: Total Antioxidant Capacity (Tac) By Abts Methodsmentioning
confidence: 99%
“…It was found to be a better source of antioxidant as compared to BHT and BHA Patel et al (2013). observed that extracts of coriander (steam distilled and oleoresin) significantly inhibited the peroxide development throughout the 21 days of storage at 80 8C as compared to the control Pawar, Gandhi, Purohit, Arora, & Singh, (2014). observed that vidarikand, shatavari and ashwagandha extracts (aqueous and ethanolic) significantly (p < .05) lowered the peroxide value throughout 21 days of storage at 80 6 1 8C as compared to the control.…”
mentioning
confidence: 99%
“…Previous studies on ghee intimated that various herb extracts prevented ghee from oxidative deterioration at addition levels of 0.5% to 1% (w/w) (Pawar et al . ,b). Furthermore, Prevention of food adulteration act (PFA) rules (1976) have limited the addition of BHA to the rate of 0.02% (w/w).…”
Section: Introductionmentioning
confidence: 97%